White matter maturation of normal human fetal brain. An in vivo diffusion tensor tractography study - Zanin, Emilie (Blackwell Publishing Inc, 2011)
We demonstrate for the first time the ability to determine in vivo and in utero the transitions between the main stages of white matter (WM) maturation in normal human fetuses using magnetic resonance diffusion tensor imaging (DTI) tractography. Biophysical characteristics of water motion are used as an indirect probe to evaluate progression of the tissue matrix organization in cortico-spinal tracts (CSTs), optic radiations (OR), and corpus callosum (CC) in 17 normal human fetuses explored between 23 and 38 weeks of gestation (GW) and selected strictly on minimal motion artifacts. Nonlinear polynomial (third order) curve fittings of normalized longitudinal and radial water diffusivities (Z-scores) as a function of age identify three different phases of maturation with specific dynamics for each WM bundle type. These phases may correspond to distinct cellular events such as axonal organization, myelination gliosis, and myelination, previously reported by other groups on post-mortem fetuses using immunostaining methods. According to the DTI parameter dynamics, we suggest that myelination (phase 3) appears early in the CSTs, followed by the OR and by the CC, respectively. DTI tractography provides access to a better understanding of fetal WM maturation.